The Holocaust and the historians - Dawidowicz, Lucy S. 1915-1990 (Harvard Univ. Press, 1981)
The author opens by providing an overview which highlights the tragic magnitude of the Holocaust. she examines the historical studies written on the Holocaust emphasizing the insufficient recording of the period by historians.